2014
DOI: 10.1007/s00261-014-0233-7
|View full text |Cite
|
Sign up to set email alerts
|

Mass-like peripheral zone enhancement on CT is predictive of higher-grade (Gleason 4 + 3 and higher) prostate cancer

Abstract: Focal mass-like peripheral zone enhancement on routine venous-phase CT is specific and predictive of higher-grade (Gleason 4 + 3 and higher) prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…The agreement between readers, as well as general performance, will increase as the training levels increase with this new technique. Similar to Glazer et al [25] and Jia et al [24], we found that DCE-CT enables the detection and differentiation of PCa in the PZ. A veritable advantage of DCE-CT compared to single-phase CT is the ability to generate MIP images and perfusion maps.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The agreement between readers, as well as general performance, will increase as the training levels increase with this new technique. Similar to Glazer et al [25] and Jia et al [24], we found that DCE-CT enables the detection and differentiation of PCa in the PZ. A veritable advantage of DCE-CT compared to single-phase CT is the ability to generate MIP images and perfusion maps.…”
Section: Discussionsupporting
confidence: 90%
“…In another retrospective study, Glazer et al reevaluated non-dynamic, contrast-enhanced CT of the abdomen and pelvis in 90 patients with PCa and 49 patients without PCa. A visual grading score of 5 increased the likelihood of a higher-grade PCa from 31% to 81% in this study population [25]. These two studies might suggest that, even in single phase pelvic CT, a PCa lesion can be detected.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Disease-free survival and risk of metastases vary greatly between lower grade (Gleason 3+3 and 3+4) and higher grade (Gleason 4+3 and above) cancer and between Gleason pattern 3+4 and Gleason pattern 4+3 tumors (811). Consequently, several authors have proposed modified scoring systems based on a quantitative Gleason grade in which the percentage of each pattern is reported or alternative grading systems such as the Prostate Cancer Prevention Trial Risk Calculator so as to more accurately reflect prognosis and reduce overtreatment (1214).…”
Section: Introductionmentioning
confidence: 99%
“…Однако впоследствии дан ный метод не вошел в клиническую практику из за широкого распространения МРТ, которая превос ходит КТ в выявлении локализованного РПЖ. Ис следования последних лет, проведенные на совре менных томографах с использованием болюсного контрастирования, подтверждают, что чувствитель ность КТ с контрастированием ниже, чем у МРТ (63 vs. 88 %), однако специфичность КТ выше (98 vs. 86 %) [5,9,13]. С 2005 г. в литературе стали появ ляться работы о возможности использования пер фузионной компьютерной томографии (ПКТ) в диагностике локализованного РПЖ [2,11].…”
Section: Introductionunclassified